PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON-EXAMPLE UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS VII SMP NU KAPLONGAN - Latifah; Efendi, Irfan; Hasanudin, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled "The Application of the Example Non-Example Learning Model to Improve Descriptive Text Writing Skills in Grade VII Students of SMP NU Kaplongan." The subjects of this study were students of grade VII A as the experimental class and students of grade VII B as the control class. This study was motivated by student inactivity in learning to write descriptive texts, lack of student abilities, and the learning model that was still not varied. The research method used in this study was an experimental study with the subjects being 31 students of grade VII A as the experimental class and 31 students of grade VII B as the control class. This study aims to determine (1) the activity of the application of the example non-example model in learning to write descriptive texts in grade VII students of SMP NU Kaplongan, (2) to determine the effectiveness of the application of the example non-example model in learning to write descriptive texts in grade VII students of SMP NU Kaplongan. Data collection in this study was by collecting data from observations and tests (pretest and posttest). The results of this study indicate an increase in student learning outcomes, with teacher activity observations scoring 85.71, categorized as very good, and student activity observations scoring 82.14, categorized as good. Thus, it is proven that the application of the example-non-example model can improve student engagement in learning to write descriptive texts in grade VII of SMP NU Kaplongan. Based on statistical calculations using the independent samples t-test, the calculated T was 4.463 and the T table was 2.000. Therefore, T (3.463) > (2.000), indicating that Ha is accepted and Ho is rejected. Thus, it can be stated that the example-non-example model is effective in learning to write descriptive texts for grade VII students of SMP NU Kaplongan in the 2024/2025 academic year.